Answer :

Let the present age of man be ‘a’ and present age of son be b.

Given, Six years hence a man’s age will be three times the age of his son and three years ago he was nine times as old as his son

⇒ a + 6 = 3(b + 6)

⇒ a = 3b + 12 ------ (1)

Also, three years ago he was nine times as old as his son

⇒ a – 3 = 9(b – 3)

⇒ a = 9b – 24 ----- (2)

Equating eq1 and eq2

⇒ 3b + 12 = 9b – 24

⇒ b = 6

Thus, a = 3b + 12 = 30

Hence age of man is 30 yrs and age of son is 6 yrs.Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

Two Stories about Flying39 mins

Transportation in One Shot42 mins

Human Reproduction in One Shot45 mins

Extraction of Metal56 mins

Outcomes of Democracy43 mins

Classification of Base55 mins

Purification of Metals60 mins

Classification of Acid44 mins

Application of Trigo Important Questions44 mins

Trigonometric Ratios of Specified Angles38 mins

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

Solve each of theRS Aggarwal - Mathematics

If 2x – 3y = 7 anRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics